Mapeo de las unidades productivas de seis cultivos en las comunidades de Cotopaxi, mediante un sistema de información geográfica. - Pilatasig Tipanluisa, Dayana Secibel (2024)
The objective of the research project was to map the productive units in the eight communities of the province of Cotopaxi. To perform a zoning of the productive units in the canton of Salcedo and Pujilí establishing the priority sectors of the main crops of the canton, determining their location, the crops they produce, the information for the work was obtained through metadata from the survey, the development of the map was done in three phases: planning, development, and completion using the geographic information system tool and Arcgis online. The analysis of the metadata identified six crops in the areas under study. In the case of corn, the highest percentage of production was identified in the community of Carrillo; in the community of Atocha it was found that there is a higher percentage of potato and melloco production due to the soil and climatic conditions they have. In the case of chocho, frejol and quinoa, it was found that there is greater diversity in Isinche de infantes de Pujilí.